2001
DOI: 10.1074/jbc.m107208200
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Mediator of Retinoid and Thyroid Hormone Receptors and Activating Signal Cointegrator-2 as Transcriptional Coregulators of the Orphan Nuclear Receptor Nur77

Abstract: For the orphan nuclear receptor subfamily that includes Nur77 (NGFI-B), Nurr1, and NOR-1, no transcriptional coregulators have been identified thus far. In this report, we found that Ca 2؉ /calmodulin-dependent protein kinase IV enhances Nur77 transactivation in cotransfections either alone or in synergy with AF2-dependent coactivator ASC-2, whereas corepressor silencing mediator for retinoid and thyroid hormone receptors (SMRT) is repressive. Interestingly, Nur77 interacted with SMRT but did not directly bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 33 publications
(33 reference statements)
0
48
1
Order By: Relevance
“…Indeed, like many other transcriptional coregulators, ASC-2 is known to be targeted by various signaling pathways (24,30,31). In other words, posttranslational modifications of ASC-2 by different signaling pathways could allow ASC-2 to preferentially interact with CoAA or CAPER, and therefore in response to steroid hormones, ASC-2 could recruit one or the other coactivator, depending on the signaling context within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, like many other transcriptional coregulators, ASC-2 is known to be targeted by various signaling pathways (24,30,31). In other words, posttranslational modifications of ASC-2 by different signaling pathways could allow ASC-2 to preferentially interact with CoAA or CAPER, and therefore in response to steroid hormones, ASC-2 could recruit one or the other coactivator, depending on the signaling context within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…ARR19 Competes with SRC-1 for Binding to Nur77-It has been reported that SRC-1 and SRC-2 can directly bind to the AF-2 and AF-1 domains of Nur77, respectively, and enhance the transcriptional activity of Nur77 (11,23). Because the AF-2 domain of Nur77 is the binding site for both SRC-1 and ARR19 (Fig.…”
Section: Arr19 Interacts With Nur77 In Vivo and In Vitro-mentioning
confidence: 99%
“…Although Nur77 has been well characterized as an immediate early response gene (2, 14 -17) and for its post-translational modifications (18 -22), coregulators involved in Nur77 transactivation are not fully characterized. Recently, steroid receptor coactivator (SRC)-1 and silencing mediator for retinoid and thyroid hormone receptors have been shown to regulate Nur77 transactivation through direct protein-protein interactions (11,23).…”
mentioning
confidence: 99%
“…For the NR4A subfamily, the AF1 appears to play the predominant role in transcriptional activation and co-factor recruitment, and its activity can be regulated by phosphorylation (21)(22)(23)(24)(25)(26). Recent results show that the AF1 directly recruits co-activators such as members of the SRC family, p300, pCAF, and DRIP205 (25,26).…”
mentioning
confidence: 99%
“…Importantly, the AF2 does not directly interact with SRCs, p300, pCAF, or DRIP205, and little is known about the regulation of its activity (12,25,27,28). However, the co-repressor SMRT, the atypical orphan receptor DAX-1, and the SUMO ubiquitin ligase PIAS␥ have been reported to interact with the LBD of either NGFI-B or Nurr1, and play a role in AF2 regulation (22,29,30).…”
mentioning
confidence: 99%